A framing analysis of organizational communications in sport for development - Kang, Seungmin; Svensson, Per G. (Managing leisure, 2023)
How do Sport for Development and Peace (SDP) organizations frame sport and development in their written organizational communication with external stakeholders? A qualitative document analysis was conducted based on textual data collected from websites of 115 organizations representing a wide range of sports and geographical locations. Findings revealed that SDP organizations frequently frame inherent, transferable, and instrumental values of sport while development was communicated through several different frames centered around sport development, hegemonic tendencies, individual development, and alternative values. These findings extend the existing knowledge base around the meanings SDP practitioners ascribe to the concepts of sport and development in their communications with external stakeholders. A taxonomy model is presented which can serve as a foundation to better understand organizational communication in SDP.